Strengthening the development of the short-rotation plantations bioenergy sector: Policy insights from six European countries. (December 2017) - Parra-López, Carlos; Holley, Martin; Lindegaard, Kevin; Sayadi, Samir; Esteban-López, Gonzalo; Durán-Zuazo, Víctor H.; Knauer, Christoph; Engelbrechten, Hans-Georg von; Winterber, Ralf; Henriksson, Annika; Lamley, Annette; Nylander, Anders; et al.
Abstract: This paper, based on a participatory methodological framework involving expert stakeholders and researchers from six European countries (Germany, Ireland, Poland, Spain, Sweden and UK), analyses the priority issues for the development of short-rotation plantations (SRP), and proposes a series of policy strategies to strengthen this development. The results indicate that there is a lack of awareness of the multifaceted benefits of SRP at the level of farmers, policy makers and public authorities. More research is required to put a value on the multifunctionality of SRP and justify its public support. Small-scale projects using established technologies are also required with energy crops introduced in a phased manner. The simultaneous dissemination of this knowledge upwards to policy makers and downwards to producers and farmers is critical in the success of SRP. Also, greater financial support on both the supply and demand side is highlighted as being necessary: on the supply side linking multifunctional benefits of SRP and targeted payments, along with increased long-term contractual arrangements between farmers and energy plant operators; demand side incentives should overcome any difference in price between fossil fuels and energy crops. Groups to lobby for the uptake and support of SRP and bioenergy are also of necessary. Highlights: Renewable energy is at the core of EU's long-term energy strategy. SRP may represent a sustainable energy source. The development of the European SRP industry is still in its infancy. New long-term policy strategies must be undertaken. R&D, knowledge transfer and financial support should be improved.